Endoscopic Treatment of Superficial Gastric Cancer: Present Status and Future - Hiroyuki Hisada; Yoshiki Sakaguchi; Kaori Oshio; Satoru Mizutani; Hideki Nakagawa; Junichi Sato; Dai Kubota; Miho Obata; Rina Cho; Sayaka Nagao; Yuko Miura; Hiroya Mizutani; et al. (Current Oncology, 2022)
Although the mortality rates of gastric cancer (GC) are gradually declining, gastric cancer is still the fourth leading cause of cancer-related death worldwide. This may be due to the high rate of patients who are diagnosed with GC at advanced stages. However, in countries such as Japan with endoscopic screening systems, more than half of GCs are discovered at an early stage, enabling endoscopic resection (ER). Especially after the introduction of endoscopic submucosal dissection (ESD) in Japan around 2000, a high en bloc resection rate allowing pathological assessment of margin and depth has become possible. While ER is a diagnostic method of treatment and may not always be curative, it is widely accepted as standard treatment because it is less invasive than surgery and can provide an accurate diagnosis for deciding whether additional surgery is necessary. The curability of ER is currently assessed by the completeness of primary tumor removal and the possibility of lymph node metastasis. This review introduces methods, indications, and curability criteria for ER of EGC. Despite recent advances, several problems remain unsolved. This review will also outline the latest evidence concerning future issues.